2010
DOI: 10.1038/eye.2010.9
|View full text |Cite
|
Sign up to set email alerts
|

Ranibizumab for retinal angiomatous proliferation in age-related macular degeneration

Abstract: Purpose To assess the 1-year functional outcome and to evaluate the morphological changes after intravitreal injections of ranibizumab in eyes affected with retinal angiomatous proliferation (RAP) due to age-related macular degeneration (AMD). Methods A prospective, non-randomized, interventional study was conducted on 26 consecutive patients with newly diagnosed RAP. All eyes were treatment naive and were randomized to receive intravitreal injections of ranibizumab for a 12-month period. After the first three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…The treatment of RAP using ranibizumab has also yielded promising results;11 12 however, few studies have reported the long-term functional and anatomical outcomes of intravitreal ranibizumab (IVR) in patients with RAP. Furthermore, a previous report concluded that geographic atrophy occurred frequently in patients with RAP after treatment 13.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of RAP using ranibizumab has also yielded promising results;11 12 however, few studies have reported the long-term functional and anatomical outcomes of intravitreal ranibizumab (IVR) in patients with RAP. Furthermore, a previous report concluded that geographic atrophy occurred frequently in patients with RAP after treatment 13.…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated by studies in literature, anti-VEGF treatment either as a monotherapy or in combination with PDT, has proved to be an efficient method of preserving visual acuity and providing anatomical success (10)(11)(12)(13)(14)(16)(17)(18)(19). Our study also presented results with preserved visual acuity and improved macular anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…travitreal antiangiogenic factor (anti-VEGF), which has been the principal method used for the last decade (10)(11)(12)). Anti-VEGF monotherapy can provide the necessary decrease in subretinal fluid, an active disease marker in clinical examination and optical coherence tomography (OCT), and also increase visual acuity (13).…”
mentioning
confidence: 99%
“…However, the success rates are debatable. There are reports of worse outcome of RAP lesions [25][26][27][28][29] as well as outcomes comparable to other CNV lesion types [6,30,31].…”
Section: Discussionmentioning
confidence: 99%